Effect of Economic Growth on CO2 Emission in Africa: Do Financial Development and Globalization Matter? - Teklie, Derese Kebede; Yağmur, Mete Han (International Journal of Energy Economics and Policy, 2024)
Carbon emissions are a global issue that has drawn policymakers' and scholars' attention. This study delved into examining the effect of globalization and financial development on carbon emissions within 52 African economies from 1997 to 2002. Energy consumption and population size were also considered controlling factors influencing carbon emissions. The study employs a two-step system-generalized method of moment (GMM) to analyze the effects, using the KOF Globalization Index and the IMF's Financial Development Index. The results indicate that carbon emissions increase with economic growth, energy consumption, and population size. Moreover, this study supports the Environmental Kuznets Curve (EKC) hypothesis. The study also reveals that globalization and its sub-indices, financial development, and financial institutions exhibit a linearly increasing role in carbon emissions. However, financial markets have a negligible effect. Nonlinearly, the squared of globalization and its sub-indices of economic and social dimensions, squared financial development, and its sub-indices exhibit a negative impact, portraying an inverted U-shaped association with carbon emissions. Meanwhile, political globalization follows a U-shaped trend. Additionally, globalization, financial development, and their sub-indices moderate carbon emissions. The implications of these findings underscore the importance of sustainable practices, green financing, and collaborative partnerships for a more environmentally sustainable path.